The relationship between mean platelet volume and flow mediated dilatation and intima media thickness of carotid artery in patients with essantial hypertension (Annals of Medical Research, 2021)
None
Keywords: Flow-Mediated Dilatation; Endothelial Dysfunction; Essential Hypertension; Carotid Artery Intima-Media Thickness; Mean Platelet Volume.